Childhood's censorship and sexuality's repression in Norbert Elias' and Michel Foucault's analyses - Santos Damazio, Crhistophe Barros dos [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2018)
This paper aims to analyze the conceptions regarding the childlike behavior control and sexuality's repression in the works of the German sociologist Norbert Elias and the French philosopher Michel Foucault. The studies about the civilizing process, developed by Elias, and the creation of speeches, analyzed by Foucault, serve as main theoretical references for this work.
Keywords: Norbert Elias; Michel Foucault; childhood; sexuality; civilization